Business Culture Attributes as Microfoundations of Retail Dynamic Capabilities: A Conceptual Framework - Mahfud (International Journal of Management, Economic, Business and Accounting, 2026)
Purpose of the study — This study aims to develop a conceptual framework that links business culture attributes to dynamic capabilities in the retail sector. Specifically, it investigates how decision tempo, collaboration/engagement, measurement/direction, and work/execution culture attributes act as microfoundations for dynamic capabilities, which in turn influence omnichannel integration and retail execution capabilities, ultimately impacting customer experience and retail performance. Research method—This is a conceptual paper that synthesizes existing literature from organizational culture and dynamic capabilities theories. The framework was developed through a rigorous literature review, focusing on the integration of cultural attributes in the context of retail management and omnichannel retailing. Propositions were derived to link cultural attributes with dynamic capabilities and retail outcomes. Result— The study proposes that the four cultural attributes significantly shape dynamic capabilities in retail organizations. These capabilities are essential for enhancing omnichannel integration and improving retail execution. Furthermore, the study suggests that complementarity (fit) among these cultural attributes strengthens capability development and that environmental factors such as market dynamism moderate these relationships. Conclusion— This paper provides a framework for understanding how cultural attributes influence retail performance through dynamic capabilities. It contributes to retail management by offering a practical approach to assessing and improving organizational culture, with implications for both academic research and managerial practice. Retail leaders can use the framework to optimize culture and enhance operational performance, particularly in the context of digital transformation.